Audiometric features in young adults with Turner syndrome. (2nd September 2017) - Bonnard, Åsa; Hederstierna, Christina; Bark, Rusana; Hultcrantz, Malou
Abstract: Objective : Hearing loss (HL) is a known problem in adults with Turner syndrome (TS). The aim of this study was to investigate audiometric features in young adults with TS and the extent of hearing aid provision. Design : Patients were recruited from the Turner centre at Karolinska University Hospital. Analysis of audiograms was made in relation to hearing aid use, a Swedish normal hearing cohort and the need for hearing rehabilitation. Study sample : Sixty-four women with TS aged 25–38 years at the time of their audiological testing. Results : Fifty-two percent had impaired hearing in at least one ear. Sensorineural hearing loss (SNHL) was the most common type of HL, most often characterised by a high-frequency loss and/or a mid-frequency dip. Conductive HL was uncommon in young adults with TS, even though 47 percent were otitis prone as children. Eight of 64 women had previously been fitted with hearing aids. Conclusions : There is undoubtedly a need for hearing rehabilitation in young adults with TS. Questions about hearing must be asked by all doctors treating women with TS to identify those in need for hearing rehabilitation, even if they have an audiogram with a normal pure tone average.